Social theory and the study of Israelite religion : essays in retrospect and prospect - Olyan, Saul M. (Resources for biblical study, 2012)
This volume assesses the past, theoretically engaged work on Israelite religion and presents new approaches to particular problems and larger interpretive and methadological questions. It gathers previously unpublished research by senior and mid-career scholars well known for their contributions in the area of social theory and the study of the Israelite religion and by junior scholars whose writing is just beginning to have a serious impact on the field. The volume begins with a critical introduction by the editor. Topics of interest to the contributors include gender, violence, social change, the festivals, the dynamics of shame and honor, and the relationship of text to ritual. The contrbutors engage theory from social and cultural anthropology, sociology, postcolonial studies, and ritual studies. Theoretical models are evaluated in light of the primary data, and some authors modify or adapt theory to increase its utility for biblical studies.